Bioelectrochemical Vs Hydrogenophilic Approach for co2 Reduction into Methane and Acetate - Gacitua-Santalices, M; Gacitua-Santalices, M (Elsevier B.V., 2020)
Methane and acetate production through CO2 reduction has been tested by using chemoautotrophic microorganisms under bioelectrochemical and hydrogenophilic conditions. For the methanogenic tests, a thermophilic anaerobic sludge has been used as inoculum while the thermal treatment of the anaerobic sludge allowed the acetogenic inoculum selection. The optimal pH has been selected through methane and acetate hydrogenophilic tests at three different pH values (5.5, 6.5, 7.5) while three different cathodic potentials (-0.7, −0.9, −1.1 V vs SHE) have been tested in bioelectrochemical experiments by using the optimum pH value. Both methane and acetate production showed higher efficiency by the use of the bioelectrochemical system instead of the corresponding hydrogenophilic tests, i.e. during the −0.9 V vs SHE bioelectrochemical condition, the efficiency for methane and acetate reached the 95 and 88% while in the hydrogenophilic tests the efficiency resulted considerably lower, with average values of 11% and 16% for methane and acetate, respectively. The higher efficiency of the bioelectrochemical system has been also confirmed by the determination of methane and acetate production rate which shown a 45 and 66% increase with respect the hydrogenophilic tests. The higher efficiency of bioelectrochemical tests has been justified by assuming a higher hydrogen mass transfer from the electrode surface to the attached biofilm. Moreover, the bioelectrochemical tests suggested the presence of a direct electron uptake for methane production, while for the acetate production, a hydrogen mediated mechanism appeared necessary. Finally, the microbial community characterization by the DGGE analysis highlighted the effectiveness of the thermal treatment for acetogens selection by methanogens inhibition. © 2020 Elsevier B.V.